Psychosocial programme for persons with spinal cord injuries - Knezović, Zvonimir (Array, 2000)
In accordance with the integral psychosocial approach, the bio-psychosocal programme has been structured. This programmes aims at helping persons with spinal cord injuries. It consisted of a broad diagnosis poll-based questionnaire, which was applied to 124 people in one Croatian region. It was also based on different types of intervention treatments applied to 68 people, all of whom had chosen one or more of these interventions according to their personal preferences. The first results have shown some positive changes regarding the grade of psychosocial adaptation and general life quality of the persons with spinal cord injuries.